Eric Horvitz Forecasts the Future - Horvitz, Eric (New Scientist Magazine, 2006)
Computation is the fire in our modern-day caves. By 2056, the computational revolution will be recognised as a transformation as significant as the industrial revolution. The evolution and widespread diffusion of computation and its analytical fruits will have major impacts on socioeconomics, science and culture.